2011
DOI: 10.2967/jnumed.111.087957
|View full text |Cite
|
Sign up to set email alerts
|

MRI Measurement of Bone Marrow Cellularity for Radiation Dosimetry

Abstract: The current gold standard for measuring marrow cellularity is the bone marrow (BM) biopsy of the iliac crest. This measure is not predictive of total marrow cellularity, because the biopsy volume is typically small and fat fraction varies across the skeleton. MRI and localized MR spectroscopy have been demonstrated as noninvasive means for measuring BM cellularity in patients. The accuracy of these methods has been well established in phantom studies and in the determination of in vivo hepatic fat fractions bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…From the results obtained in this study, we presumed that it shows a similar trend among fat image volume from a 4.7 T MRI, histology from adipocytes, and fat mass gain from mice. Some recent studies showed that MRI and localised MR spectroscopy are used to confirm the amount of body fat in obese mice or for phantom studies and the determination of in vivo hepatic fat fractions . In this study, by using staining techniques, we observed that treatments with green pepper juice tended to reduce the amount of adipose tissue; and by using non‐invasive MRI in a mouse model receiving a high‐fat diet with green pepper juice we showed a decrease in abdominal fat mass.…”
Section: Discussionsupporting
confidence: 53%
“…From the results obtained in this study, we presumed that it shows a similar trend among fat image volume from a 4.7 T MRI, histology from adipocytes, and fat mass gain from mice. Some recent studies showed that MRI and localised MR spectroscopy are used to confirm the amount of body fat in obese mice or for phantom studies and the determination of in vivo hepatic fat fractions . In this study, by using staining techniques, we observed that treatments with green pepper juice tended to reduce the amount of adipose tissue; and by using non‐invasive MRI in a mouse model receiving a high‐fat diet with green pepper juice we showed a decrease in abdominal fat mass.…”
Section: Discussionsupporting
confidence: 53%
“…Insufficiency fractures and hematologic toxicity are clinically important complications of radiation therapy . Bone marrow water/fat quantification has been proposed for measuring the patient‐specific bone marrow cellularity distribution in radiation therapy planning . The quantitative evaluation of radiation therapy‐associated changes has only been performed in a limited number of studies.…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…155 Bone marrow water/fat quantification has been proposed for measuring the patient-specific bone marrow cellularity distribution in radiation therapy planning. 156 The quantitative evaluation of radiation therapy-associated changes has only been performed in a limited number of studies. Changes of irradiated bone marrow reflecting fatty replacement are traditionally recognized by prolonged T 1 relaxation times.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Bone marrow fat can be quantified by magnetic resonance spectroscopy (MRS), which utilizes the resonance frequency of protons to differentiate fat from water; the ratio provides an assessment of chemical composition of bone marrow [14]. In animal studies, the volume of bone marrow fat by biopsy strongly correlates ( r =0.9) with fat volume assessed by MRS [15]. MRS is currently used for quantifying the bone marrow fat in the normal population, with lumbar spine being the most studied site [16].…”
Section: Introductionmentioning
confidence: 99%